2012
DOI: 10.1016/j.cell.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Genetically Modified Mice by Oocyte Injection of Androgenetic Haploid Embryonic Stem Cells

Abstract: Haploid cells are amenable for genetic analysis. Recent success in the derivation of mouse haploid embryonic stem cells (haESCs) via parthenogenesis has enabled genetic screening in mammalian cells. However, successful generation of live animals from these haESCs, which is needed to extend the genetic analysis to the organism level, has not been achieved. Here, we report the derivation of haESCs from androgenetic blastocysts. These cells, designated as AG-haESCs, partially maintain paternal imprints, express c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
238
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(261 citation statements)
references
References 46 publications
(66 reference statements)
17
238
0
1
Order By: Relevance
“…In the mouse study, approximately 16-21% of haploid zygotes developed to the blastocyst stage, which was significantly lower than was observed for the diploid zygotes. 7 This trend is in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the mouse study, approximately 16-21% of haploid zygotes developed to the blastocyst stage, which was significantly lower than was observed for the diploid zygotes. 7 This trend is in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…7 Therefore, haploid androgeneic ES cells provide a potential method to resolve infertility caused by azoospermia and could also be used as a transgenic tool. Several labs have reported haploid mouse ES cells, [5][6][7] but not haploid human ES cells, thereby limiting further application in humans. One key limitation lies in obtaining haploid embryos or blastocysts for ES derivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haploid embryonic stem cells (haESCs) have been recently generated from parthenogenetic (PG) or androgenetic (AG) blastocysts of different mammals, including mouse, rat and monkey, enabling genetic screening at both cellular and organism levels [1][2][3][4][5][6]. However, whether haESCs can be generated from human remains unknown.…”
Section: Dear Editormentioning
confidence: 99%
“…Sperm derived from these transplanted germ cells are capable of fertilizing oocytes in vitro, and further generating viable offspring that are developmentally normal and fertile [10]. More interestingly, a very recent study showed that androgenetic haploid mouse ESCs can be derived and genetically manipulated in vitro [11]. Interestingly, these cells, when injected into oocytes, can give rise to fertile adult mice, suggesting that these sperm-like ESCs can be used as a genetically tractable alternative for in vitro fertilization [11].…”
mentioning
confidence: 99%